Genetic testing in male infertility – reassessing screening thresholds. Issue 3 (May 2020) - Liu, James L.; Peña, Vanessa; Fletcher, Sean A.; Kohn, Taylor P.
Abstract : Purpose of review: Genetic testing in male infertility is an essential part of the process of diagnosis. Genetic abnormalities, such as Y-chromosome microdeletion, chromosomal abnormalities and mutations for cystic fibrosis, can all negatively impact a male's fertility and can be tested for during a fertility evaluation. Both Y-chromosome microdeletion and chromosomal abnormalities increase in prevalence as sperm concentrations decrease, and azoospermic men have the greatest frequency of genetic abnormalities. Recent findings: These genetic abnormalities can also be found in oligospermic men; however, on the basis of several recent studies, the prevalence of genetic abnormalities is lower in oligospermic men than previously thought. Summary: The current screening thresholds are devised from the previously determined prevalences and have not been revised based on the emerging data; thus, in this review of the literature, we will discuss this new evidence and whether screening thresholds should be changed.